Limites entre indivíduo e governo na teoria política de Locke - Dores, João Alberto Araújo das (2023)
What is the “individual”? On the other hand, what is its natural role in its life in a political context? How does the individual relate to the property that appeals to him or her as the basis of its existence? These are questions that have been asked by philosophy since its inception and have been framed throughout its history. Several philosophers have addressed this question in various interesting ways. Locke was no exception. Like others, he was seized by the complexity of the issue and approached it through the analysis of what causes the emergence of civil society, the origin of its power and its ideal extension. The purpose of this research is to understand and clarify John Locke's efforts and, with him, to describe what the individual is. Also, define its role in relation to itself and others, before and after the establishment of its civil society pact. In this respect, the government's role has also been defined. How should its powers be exercised? If the political pact should be beneficial to everyone, should it ignore the possibility of abuse? The response can hardly be anything but negative. But how to avoid them? Does the legislature have to regulate everything? If such an option is unreasonable and thus dangerous, what constraints should individuals pay special attention to when delimiting civil government? Such questions are imperative and if not genuinely understood, may cause the individual to see his autonomy subdued and used potentially against himself, establishing an unlimited and absolute authority. In light of this, Locke began an investigation, offering a few answers. Therefore, if we can speak of an actual state of nature and a subsequent transition to a political state in which many individuals choose to participate, what can we effectively infer from this? For Locke, this does not imply that the former is necessarily better than the latter, nor does it imply that the latter, because of its benefits, is intrinsically better than the former, paving a way that could be considered more “righteous”. The key is to understand these conditions and extract from them the different forms of human existence.